Evaluation of the Amount and pH of Saliva of Edentulous Patients before and after Using Probiotics. - Dandekeri, Shilpa; Dandekeri, Savita; Prabhu, Uma Mayoor; Shetty, Nitesh; E, Nagaraj (Bangladesh Journal of Medical Science, 2023)
Introduction: Elderly individuals, with or without full dentures, have often been offered probiotics to aid with digestion. An increase in saliva production due to the use of probiotics is noted. Therefore, it was decided to conduct this research to determine the effects of probiotics on the quantity and pH of saliva in patients who are entirely denture-free after 60 days of use. Aim: The goal of this study is to evaluate whether or not probiotic supplementation causes an increase in saliva production in edentulous individuals. Methods: Patients with missing teeth were used in the research. The pH was measured after collecting baseline amounts and baseline amounts of both unstimulated and stimulated saliva. Then, once a day for 60 days, patients took capsules containing probiotics at 3.3 107 CFU/g. Patients' saliva was collected, and its volume and pH were determined for comparison to the initial measurements. Results: After 60 days of taking probiotics, the average amount of saliva, both unstimulated and stimulated, is higher than it was at the beginning of the study. P <0.001 indicates a statistically significant difference. After 60 days, the mean pH was somewhat higher than it had been at the start (0.010). Conclusion: Those with xerostomia or hyposalivation may benefit from taking probiotics, as this study found that they increased saliva production in patients who were completely edentulous. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.72-77